PENERAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM MENCAPAI SUSTAINABLE GROWTH (STUDI KASUS PT SUPRAMA) - Bintari, Revita Novi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to evaluate the implementation of Corporate Social Responsibility. CSR as one of important elements in business in order to reach sustainable growth. The result of the research indicates that PT Suprama has been implementing the CSR whether internally or externally. The implementation of CSR on PT Suprama has influence the sustainable growth indirectly. This can be proved by the improvement of sales percentage, reputation, and the expansion of PT Suprama sales territory from year to year.Keywords: corporate Social Responsibility, Sustainable Growth, Internal and External CSR, Sustainable Report.